HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH SAAT HOSPITALISASI - Nunung " Oktavien; Riri " Novayelinda; Jumaini " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The experiences of hospitalization leaded to stress and anxiety. With the result that his research aim to identify relationship between patient social support with anxiety level in hospitalized pre-school age children (3-5 years) in space flamboyant Arifin Achmad Pekanbaru. Design of this study was descriptive correlation with cross sectional approach. The sample taken with purposive sampling technique as many as 44 respondents. Measuring instrument used was a questionnaire for the variable social support parents and questionnaires Spence Children Anxiety Scale (SCAS) to the variable level of anxiety children. The analysis used univariate analysis to determine the frequency distribution and bivariate using Chi Square. 63.6% of children received social support of parents positively with the level of anxiety was 70.5%. The statistical results obtained p value (0.006) < alpha (0.05), so that the conclusion there is relationship between parent social support with anxiety level in hospitalized pre-school age children (3-5 years) in space flamboyant Arifin Achmad Pekanbaru. According to this research result adviced for health employee to increasing the psychosocial nursing intervention and remind to parents that the importance of parents social support to minimalizing children anxiety when hospitalized. Keyword: Parents social support, hospitalized, anxiety, pre-school